A case report of xanthogranulomatous osteomyelitis of the distal ulna mimicking a malignant neoplasm - Lee, Seung Hyun (International Scientific Literature, Inc., 2013)
Patient: Male, 59 Final Diagnosis: Xanthogranulomatous osteomyelitis Symptoms: Painful swelling in the wrist Medication: Drug history of antifulgal agents Clinical Procedure: Excisional biopsy Specialty: Radiology OBJECTIVE: Rare disease BACKGROUND: Xanthogranulomatous inflammation is a chronic inflammatory disease in which bone involvement is extremely rare. Bone involvement of xanthogranulomatous inflammation, termed xanthogranulomatous osteomyelitis (XO), often presents as a mass-like lesion extending to adjacent structures, which can mimic infiltrative carcinoma. CASE REPORT: We present a case of XO in the ulna, which mimicked a neoplasm. A 59-year-old man presented with a 2-month history of painful swelling in the right wrist. Plain radiography and CT showed an osteolytic lesion at the distal ulna. MRI revealed a soft-tissue mass with lobulated margins and contrast enhancement. Intense uptake in bone scan and PET suggested malignancy. An excisional biopsy from the representative area resulted in a pathology diagnosis of XO. CONCLUSIONS: Gross and radiologic manifestations of XO can mimic neoplasm. XO generally has benign prognosis, contrary to malignant bone tumor. Therefore, biopsy and histopathological confirmation are necessary for proper management.